1999
DOI: 10.1038/sj.jea.7500065
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cigar smoking on indoor levels of carbon monoxide and particles

Abstract: To provide new information on environmental tobacco smoke ( ETS ) levels from cigars, we conducted three types of experiments: ( 1 ) Measurements of carbon monoxide ( CO ) during 15 controlled experiments in an office where several cigar brands were machine -smoked; ( 2 ) Measurements of CO or respirable suspended particles ( RSP ) and particle -bound polycyclic aromatic hydrocarbons ( PAH ) in a residence where two cigars were smoked by a person; and ( 3 ) Measurements of CO during two studies at cigar social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 20 publications
3
14
0
1
Order By: Relevance
“…Klepeis et al (1999) report an average of 155 mg/gsmoked for 10 different cigars with a range of 82 to 200 mg/gsmoked, values which are comparable to our results.…”
Section: Estimates Of Size-integrated Emission Factorssupporting
confidence: 81%
“…Klepeis et al (1999) report an average of 155 mg/gsmoked for 10 different cigars with a range of 82 to 200 mg/gsmoked, values which are comparable to our results.…”
Section: Estimates Of Size-integrated Emission Factorssupporting
confidence: 81%
“…The average PAS-to-RSP conversion factor of 0.83 ng g Ϫ1 , which we observed in the present study for the PAS monitor's response to smolder-smoked Marlboro cigarette emissions, implies that 0.083% of the emitted particle mass consists of particulate PAH. Our value for the conversion factor is similar to a value of 0.8 ng g Ϫ1 observed by Repace 25 in a casino and values of 1 and 0.8 -1.3 ng g Ϫ1 observed in two of our previous studies, 26,27 which used an older version of the PAS monitor (Model PAS 1000i, EcoChem, Inc.). We found that the older PAS 1000i monitor's response had to be reduced by a factor of 10 relative to the PAS 2000CE because of the fact that the 1000i uses a krypton bromine ultraviolet (UV) lamp, whereas the 2000CE uses a mercury vapor UV lamp.…”
Section: Notessupporting
confidence: 66%
“…In the present study, we observed PZB particle mass peaks in the living room and bedroom of approximately 50 and 200 g m Ϫ3 , respectively, which are similar to peak values that we observed in previous real-time monitoring studies of cigar and cigarette smoking in homes. 26,30 The average OTS particle concentrations that we observed during each experiment across all of the distances were 10 -22 g m Ϫ3 for the NEPH, 18 -29 g m Ϫ3 for the GRIMM, and 38 -61 g m Ϫ3 for the PAS, with overall averages of 15, 22, and 50 g m Ϫ3 , respectively (as shown in Table 6). The overall average indoor SHS concentrations, when the fan was not operating and at distances of 0.25 and 0.5 m only, were 30 -35 g m Ϫ3 in the living room and 46 -106 g m Ϫ3 in the bedroom for the different types of instruments.…”
Section: Outdoor Versus Indoor Concentrationsmentioning
confidence: 94%
“…Emission factor-presented as microgram of pollutant emitted per gram of coil burned-can be obtained from the emission rate divided by the burn rate. Table 4 lists a comparison of the emission factors of some pollutants found in the mosquito coil smoke with those found in environmental tobacco smoke (ETS) (Daisey et al 1998;Klepeis et al 1999). Incorporating the emission factors, coil weight, and cigarette weight (0.55 g/cigarette, excluding the filter), we derived ETS equivalents for all the tested mosquito coils.…”
Section: Resultsmentioning
confidence: 99%